Maternal age affects offspring nutrient dynamics. (August 2017) - Muller, Doriane; Giron, David; Desouhant, Emmanuel; Rey, Benjamin; Casas, Jérôme; Lefrique, Nicolas; Visser, Bertanne
Graphical abstract: Highlights: Macronutrient levels decrease with age in parasitic wasps. Mothers reduce egg provisioning with age. Age of the mother affects nutrient dynamics in developing offspring. Reduced egg provisioning negatively affects nutrient levels in adult female offspring. Abstract: The internal physiological state of a mother can have major effects on her fitness and that of her offspring. We show that maternal effects in the parasitic wasp Eupelmus vuilleti become apparent when old mothers provision their eggs with less protein, sugar and lipid. Feeding from a host after hatching allows the offspring of old mothers to overcome initial shortages in sugars and lipids, but adult offspring of old mothers still emerged with lower protein and glycogen quantities. Reduced egg provisioning by old mothers had adverse consequences for the nutrient composition of adult female offspring, despite larval feeding from a high-quality host. Lower resource availability in adult offspring of old mothers can affect behavioural decisions, life histories and performance. Maternal effects on egg nutrient provisioning may thus affect nutrient availability and fitness of future generations in oviparous animals.